STRESS DAN INSOMNIA PADA MENOPAUSE - Dwi Syalfina, Agustin; Hadi Kusuma, Yudha Laga (SEKOLAH TINGGI KESEHATAN MAJAPAHIT MOJOKERTO, 2018)
AbstractMenopause is an important period in the final period of female reproduction. Menopause period occurs Hormonal changes that occur during menopause, namely reduced inhibitin substances produced by the ovaries causing an increase in FSH (follicle stimulating hormone) followed by an increase in estrogen hormones and testosterone. Itâs causes complaints of biopsychosocial changes such as changes in mood, anxiety, sexual dysfunction, stress, forgetfulness and sleep disorders. The purpose of this study was to analyze the effect of stress and the incidence of insmonia in menopausal women. This study used an analytical method of analytic epidemiological research using a cross sectional. The independent variable in this study is stress and the variable depends is menopause insomnia. The study population was all menopausal women with the sampling technique used for sampling was simple random sampling. This research was conducted in Sumbertebu Village, Bangsal District, Mojokerto Regency. The data collection research used the Depression Anxiety Stress Questionnaire (DASS 42) for the measurement of Stress events and the Pittsburgh Sleep Quality Index (PSQI) to assess the respondent insomnia status. General data and special data after data tabulation is then analyzed using univariate and bivariate data analysis. Risk factors that significantly influence menopausal insomnia are work (P value = 0.003; PR = 3.938; 95% CI = 1.566-9.899) and stress (P value = 0.003; PR = 4.011; 95% CI = 1.553-10.3362). The dominant risk factors affecting insomnia were work (P value = 0.008; PR = 4.203; 95% CI = 1.463-12.079). Health workers are expected to improve health education about physiological and psychological changes at menopause, handling complaints during menopause, gender in menopausal women in gender roles in the family.Keywords: Risk factor, Stress, Insomnia, Menopause